Book Review: Media Law in New Zealand - Price, Steven (Victoria University of Wellington Law Review, 2005)
This article is a book review of John Burrows and Ursula Cheer Media Law in New Zealand (5 ed, Oxford University Press, Melbourne, 2005) (655 + Ixxvii Pages). The book is a lucid and comprehensive compilation of the disparate laws affecting the media in New Zealand, and some significant steps toward making sense of media law as a whole. Price argues that the emergence of media law as a legitimate field of study in New Zealand owes much to this book. The authors elucidate the law rather than evaluate it, as they are designed to help journalists and media lawyers navigate their way around legal pitfalls by providing practical advice. Price expresses weariness over the fact that the book contains dozens of examples of vexed statutory and common law issues whose resolutions ought to be informed by the New Zealand Bill of Rights Act 1990 (’BORA’), and that a burgeoning BORA jurisprudence will oblige the authors to include more on the BORA right to freedom of expression in later editions of the text. Until the law becomes more principled and coherent, however, Price concludes that the book’s guidance remains indispensable.